A Simple Cost-Effective Method of Microsurgical Simulation Training: The Turkey Wing Model - Bates, Benjamin J.; Wimalawansa, Sunishka M.; Monson, Benjamin; Rymer, Michael C.; Shapiro, Ryan; Johnson, R. Michael (Journal of Reconstructive Microsurgery, 2013)
The rat femoral artery (RFA) anastomosis model has been the gold standard in microsurgical simulation training. While effective, live animal use requires animal use committee regulation and costly maintenance. Our institution's animal laboratory is remote to the hospital, limiting access by our busy surgical residents with their limited duty hours. We present an alternative convenient, cost-effective model. Ten frozen turkey wings were divided into distal and proximal segments. Vessel diameter, length, and anastomosis perfusion were assessed. Proximal brachial arteries (“humeral” segments) measured 8.85 ± 1.14 cm long with diameter 1.69 ± 0.27 mm. Distal brachial arteries (“forearm”) measured 10.5 ± 2.06 cm long with diameter 1.25 ± 0.25 mm. An 8-lb box (∼20 wings) cost $13.76. Separate use of the segments provides two training sessions with $0.35 per session effective cost. Our average cost for RFA microsurgical training sessions was $120 dollars for a single rat 2-hour session and $66 per rat if a maximum crate load of six rats was used. Besides significant cost, not all training programs are equipped to house, care for, and use rats in microsurgical training. We now use turkey wings for microvascular training. They are cheap, abundant, readily accessible for training, and consistent with tissue quality and vessel size approximating human systems.
Keywords: turkey wing; microsurgery model; microvascular anastomosis; cost analysis; vessel characteristics